Przygotowanie dzieci do pobytu w żłobku w opinii rodziców i opiekunów w żłobkach - Ewelina Świdrak (Problemy Wczesnej Edukacji)
Entrusting each child to the nursery is a difficult task for both the child, parents and the staff of the institution. The article presents the results of research aimed at distinguishing and assessing the effectiveness of activities aimed at preparing children under three years of age to stay in a nursery according to parents and nurses in nurseries. Among the activities preparing children to stay in a nursery, the following were distinguished: behaviors aimed at getting to know the nursery, behaviorscombining the home and nursery environment, and behaviors creating a positive atmosphere around the institution, also behaviors that constitute closer and further preparation for a stay in a nursery. The research shows that parents who are preparing children to nursery stay mostly use behaviors aimed at getting to know the nursery, e.g. talking about the nursery, which are a part of closer preparation, but in the carers’ opinion, it would be more effective to make the home rhythm similar to that in the nursery and to create a positive atmosphere around the institution.